Isolation and Identification of Indigenous Plant Growth Promoting Rhizobacteria from Himalayan Region of Kashmir and their Effect on Improving Growth and Nutrient Contents of Maize (Zea Mays L.) - Zahid, Mahwish (Frontiers in Microbiology, 2015)
IIntroduction and exploitation of plant growth promoting rhizobacteria (PGPR) in agro-ecosystems enhance plant-microbes interactions that may affect ecosystems sustainability, agricultural productivity and environmental quality. The present study was conducted to isolate and identify PGPRs associated with maize (Zea mays L.) from twenty sites of Himalayan region of Hajira-Rawalakot, Azad Jammu and Kashmir (AJK), Pakistan. A total of one hundred isolates were isolated from these sites, out of which eight (HJR1, HJR2, HJR3, HJR4, HJR5, MR6, HJR7, HJR8 ) were selected in vitro for their plant growth promoting ability (PGPA) including phosphorus solubilization, indole acetic acid (IAA) production and N2 fixation. The 16S rRNA gene sequencing technique was used for molecular identity and authentication. Isolates were then further tested for their effects on growth and nutrient contents of maize (Zea mays L.) under pouch and pot conditions. The 16S rRNA gene sequencing and phylogenetic analysis identified these isolates belong to Pseudomonas and Bacillus genera. The isolates promoted plant growth by solubilizing soil P which ranged between 19.2 and 35.6 µgmL−1. The isolates HJR1, HJR2, HJR3 and HJR5 showed positive activity in acetylene reduction assay showing their N2-fixation potential. All eight isolates showed the potential to produce IAA in the range of 0.9−5.39 µgmL−1 and promote plant growth. Results from a subsequent pot experiment indicated PGPRs distinctly increased maize shoot and root length, shoot and root dry weight, root surface area, leaf surface area, shoot and root N and P contents. Among the eight isolates, HR3 showed a marked P-solubilizing activity, plant growth-promoting attributes, and the potential to be developed as a biofertilizers for integrated nutrient management strategies